Why did Uber China fail in China? – Lessons from Business Model Analysis - Yunhan Liu; Dohoon Kim (International Telecommunications Society (ITS), 2018)
The ride-hailing platform presents an on-demand business model on the basis of business ecosystems in the era of the sharing economy. The ride-hailing platforms became popular and common around the world as a sustainable option that complements the public transportation services. This article presents a case study that analyzes the intense competition between global giant Uber and Didi Chuxing in Chinese ride-hailing market. First, employing the Canvas model, we compare and analyze the characteristics of the business model of the two platforms. Our analysis and comparisons of the strategic positioning and implementation of the two platforms with respect to the major building blocks of the Canvas model finds out the success factors of Didi as well as the sources of failure of Uber. For example, although both Uber and Didi provided similar service offerings covering diverse market segments from low- to high-ends, Uber's mismatches between its strategic focus on the high-end premium segment and service operations proved to be a mistake. On the other hand, Didi operated its business more efficiently by providing a wide range of service offerings and leveraging the two-side market properly. As a result, Didi has grown successfully as a one-stop transportation platform, which is well suited to the Chinese market. This study provides important insights into business model innovations in the sharing economy and implications for the evolution of future transportation platforms.
Keywords: 330; Sharing economy; Ride-hailing platform; Canvas model; Uber China; Didi Chuxing